Modifikasi Permukaan Elektroda Karbon Menggunakan CuS@rGO-Nafion dan Uji Kinerja Elektroda pada Aplikasi Sensor Hidrazina - Dian Kharismadewi; Sri Martini (LPPM Politeknik Jambi, 2022)
Hydrazine is a dangerous chemical compound that is widely used in various industries. The presence of this compound in the waters resulting from the disposal of industrial waste must be monitored and controlled for its presence. For this reason, a sensor is needed that can be used to detect the presence of this compound in the waters. Commercial carbon electrodes are environmentally friendly materials and are relatively cheap to be used as potential sensor materials, but these materials have low electrochemical activity and are hydrophobic. To increase the electrochemical activity of the carbon electrode, modifications were carried out using CuS-Nafion and CuS@rGO-Nafion materials which were synthesized through solvothermal reactions and dropped-casting on the surface of the carbon electrodes. The modification was successfully carried out which was shown by the results of scanning electron microscopy which had a high response to the hydrazine compound shown from the results of cyclic voltammetry (CV) analysis. The best result is shown by carbon electrode modified using CuS@rGO-Nafion materials. The electrochemical impedance spectroscopy (EIS) results showed excellent results where the Rct value was 2178 Ω which could facilitate high electron transfer on the modified electrode surface.